W jakim stopniu możliwe jest ukształtowanie kompetencji w komunikacji interkulturowej w procesie przyswajania języka obcego - Woźniewicz, Władysław (Studia Rossica Posnaniensia, 2010)
The author justifies the rudimentary thesis of the paper: in the circumstances of neophilological training the acquisition of skills of respectable intercultural communication is limited. The boundaries of these limitations are given by: 1) the reduction of the use of foreign language to a basic linguistic competence, 2) the restriction of domains of communication mainly to behavioral activities, 3) socio-cultural requirement of obeying norms of political correctness, 4) the certain level of feeling of foreignness in the interpersonal relations.